PERAN LITERASI MANUSIA DALAM MENINGKATKAN PARTISIPASI SOSIAL WARGA DESA SAMBIREJO TIMUR - Rizky Seni Utami; Nurjannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the role of human literacy in enhancing social participation among residents of Sambirejo Timur Village. Human literacy is understood as an individual’s ability to comprehend human values, build social interactions, and demonstrate collective responsibility and social awareness within the community. This research employed a qualitative approach with a descriptive design. The research subjects included village residents, community leaders, and village officials. Data were collected through observation, in-depth interviews, and documentation. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing.The findings indicate that human literacy plays a significant role in improving social participation among community members. The aspect of social responsibility showed the highest percentage at 90.0%, followed by cooperation and social concern, each at 86.7%. Empathy and tolerance were categorized as good, while social communication and conflict resolution showed relatively lower percentages. These results suggest that human literacy strengthens social awareness and solidarity within the village community, although further efforts are needed to enhance communication skills and conflict management. Overall, human literacy serves as an essential foundation for building a participatory, harmonious, and empowered rural community.